Perilaku ghasab di Pondok Pesantren Darul Lughah Wal Karomah Sidomukti Kraksaan Probolinggo dan antisipasinya - Arifin, Syamsul; Yazid Adnan Quthny, Abu (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2024)
This research discusses ghasab at the Darul Lughah Wal Karomah Islamic Boarding School, Sidomukti, Kraksaan, Probolinggo. This research aims to reveal the causes of acts of ghasab at the Darul Lughah Wal Karomah Islamic Boarding School, as well as anticipating what can be offered to overcome this ghasab culture. The life of students in a religious environment does not mean that their behavior does not conflict with religious values or norms that apply to society. Islamic boarding school regulations that are set do not necessarily mean that student behavior is always normal and in line with the objectives of the regulations. Various forms of social deviation among students occur and cause problems for Islamic boarding schools. One of these deviant behaviors is ghasab. This research is qualitative in nature. The subjects of this research included caregivers, administrators, ustadz, and students. Data collection was carried out using observation, interviews and documentation methods. Data analysis was carried out by interpreting the data using a phenomenological approach and then drawing descriptive conclusions. The results of the research show: 1) Ghasab behavior at PP Darul Lughah Wal Karomah is caused by 2 factors, namely individual factors: weak awareness of students not to commit ghasab, liking to belittle things that are ghasab, traditions inherited from the previous environment (Islamic boarding school), lack of deterrent effect in action. . Environmental Factors: Lack of role models, too close interaction patterns. The anticipation or solutions provided are: changing perceptions about ghasab, setting an example not to commit ghasab, making regulations about ghasab that create a deterrent effect for students.